Spatial Distribution, Temporal Changes, and Knowledge Gaps in Basking Shark (Cetorhinus maximus) Sightings in the California Current Ecosystem - McInturf, Alexandra G.; Muhling, Barbara; Bizzarro, Joseph J.; Fangue, Nann A.; Ebert, David A.; Caillaud, Damien; Dewar, Heidi (Frontiers in Marine Science, 2022)
Among the largest fish species, the basking shark (Cetorhinus maximus) is found circumglobally in temperate and tropical waters. Though historical documents have recorded their presence in the California Current Ecosystem (CCE), basking sharks are now only rarely observed in this part of their range. We compiled recent and historical data from systematic surveys (1962–1997) and other sources (1973–2018) to (i) examine temporal patterns of basking shark sightings in the CCE, and (ii) determine the spatial, temporal, and environmental drivers that have affected basking shark presence and distribution here for the last 50 years. We first calculated variation in basking shark sightings and school size over time. We then generated species distribution models using the systematic survey data and evaluated the performance of these models against the more recent non-systematic sightings data. The sightings records indicated that the number of shark sightings was variable across years, but the number and probability of sightings declined in the mid-1980s. The systematic survey data showed up to nearly 4,000 sharks sighted per year until the 1990s, after which there were no sightings reported. In parallel, there was more than a 50% decline in school size from the 1960s to the 1980s (57.2 to 24.0 individuals per group). During the subsequent decades in the non-systematic data (>1990), less than 60 sharks were sighted per year. There were no schools larger than 10 reported, and the mean school size in the last decade (2010s) was 3.53 individuals per group. Low sea surface temperature and high chlorophyll a concentration increased sightings probability, and prevailing climatic oscillations (El Nino-Southern Oscillation index, North Pacific Gyre Oscillation, Pacific Decadal Oscillation) were also correlated with basking shark presence. Lastly, we observed a significant shift in the seasonality of sightings, from the fall and spring during the systematic survey period to the summer months after the 2000s. We conclude by offering suggestions for future research and conservation efforts; specifically, coordinating the documentation of fisheries mortalities and sightings throughout the Pacific basin would facilitate more robust population estimates and identify sources of mortality. Additionally, monitoring shark fin markets and developing region-specific genetic markers would help ensure that convention on international trade in endangered species (CITES) regulations are being followed.